Effectiveness of sports specific circuit training and high intensity interval training on aerobic capacity in male basketball players. - AVUNOORI MALLESH,; SURESH .T.N, (International Journal of Pharma and Bio Sciences, 2018)
To find out the effectiveness of Sports Specific Circuit Training and High Intensity Interval Training on aerobic capacity in male basketball players. Quasi experimental study design. Subject: 40 subjects of basketball players with age group 18 – 25 years of male gender, having agility score of <11.5 and V – sit and reach scores plus or above half inch from the point of zero. 20 subjects in the group A received Sports Specific Circuit Training and 20 subjects in group B received High Intensity Interval Training. Aerobic Capacity (VO2 Max). The results of this study shows the statistical significant changes in improving aerobic capacity (VO2Max).It is concluded that there is statistically significant improvement in aerobic capacity High Intensity Interval Training when compared to Sports Specific Circuit Training in male basketball players.